The The Phenomenon of Labors Migration in Semarang City - Silalahi, Harini Triana; Iskandar, Deden Dinar (Journal of Economic Education, 2024)
This research aims to analyze the factors that influence labors migration in the city of Semarang. This research uses Sakernas data for 2023 and uses logistic regression analysis with a total of 4,876 respondents. The results of this research show that: (1) The wage level has a positive and significant effect on the opportunities for Semarang City labors to undertake shuttle migration. (2) The level of education has a positive and significant effect on the opportunities for Semarang City labors to undertake shuttle migration. (3) Age has a positive and insignificant effect on the opportunity for Semarang City labors to undertake shuttle migration. (4) Gender has a positive and significant effect on the opportunities for Semarang City labors to undertake shuttle migration. (5) Marital status has a positive and insignificant effect on the opportunity for Semarang City labors to undertake round-trip migration. (6) The employment sector has a positive and significant effect on the opportunities for Semarang City labors to undertake shuttle migration